Maintaining The Environment Using AI in Death Language Era - Erlanda, Julhelmi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
AbstractLocal language cultures that are rich in natural knowledge are becoming extinct. The extinction of these languages certainly increases the threat to the ecosystem. As a language model, AI can create new language trends that support language extinction. However, the author also provides a series of concrete steps to use AI as a language digitization effort. With an ecolinguistic-ecodigital approach and through computational studies of language, AI is expected to contribute to language rescue. With these language revitalization steps, human-human language interactions in the community, humans with nature are better facilitated. The interactional relationship is considered to ensure environmental sustainability.Keywords: artificial intelligence, ecodigital, ecolinguistic, language revitalizationAbstrakÂ Budaya bahasa lokal yang kaya akan pengetahuan alam mulai punah. Kepunahan bahasa-bahasa ini tentu meningkatkan ancaman terhadap ekosistem. Sebagai sebuah model bahasa, AI dapat menciptakan tren bahasa baru yang mendukung kepunahan bahasa. Namun, penulis juga memberikan serangkaian langkah konkret untuk menggunakan AI sebagai upaya digitalisasi bahasa. Dengan pendekatan ekolinguistik-ekodigital dan melalui studi komputasi bahasa, AI diharapkan dapat berkontribusi dalam penyelamatan bahasa. Dengan langkah-langkah revitalisasi bahasa tersebut, interaksi bahasa manusia-manusia di masyarakat, manusia dengan alam menjadi lebih terfasilitasi. Hubungan interaksional tersebut dianggap dapat menjamin kelestarian lingkungan.Kata Kunci: kecerdasan buatan, ekodigital, ekolinguistik, revitalisasi bahasa, linguistik komputasi